Representation of Ancient Turks in Isajon Sulton’s Bilge Khagan - Ainur Akhmetova; Mavlon Bobokhonov (Asiatic: IIUM Journal of English Language and Literature, 2025)
Given its status as a Turkic-speaking nation of Central Asia, Uzbekistan provides a pertinent case study for the examination of contemporary portrayals of historical narratives, particularly those pertaining to the ancient Gokturks or Kök-Türks (ancient Turkic people), within the context of post-independence Uzbek literature. The present study examines the depiction of Turkic identity and ideas in Isajon Sulton’s novel Bilge Khagan from a postcolonial perspective, using pragmatic discourse analysis, new criticism, reader-response theory, and comparative literary methods. The findings demonstrate that Turkic elements, or Turkisms, integrated into the post-Soviet literary tradition of Turkic-speaking nations. These literary endeavours signify a deliberate attempt to decolonise cultural memory and revitalise Turkic heritage. The juxtaposition of Uzbek and Kazakh motifs is employed by authors to convey shared history, traditions, values, and the heroic legacy of the Gokturks, often with ideological objectives in mind. During the Soviet era, there was a considerable degree of distortion and suppression of Turkic literary and historical legacies. Orkhon-Yenisei inscriptions including Bilge Khagan, Kul Tigin, and Tonyukuk underpin modern Turkist literature. This article analyzes the reinterpretation of Bilge Khagan’s period in the second Ancient Turkic Khaganate, highlighting the author’s post-colonial interpretation of Turkism for contemporary readers.